Phage-encoded carbohydrate-interacting proteins in the human gut - Rothschild-Rodriguez, Daniela; Hedges, Morgen; Kaplan, Merve; Karav, Sercan; Nobrega, Franklin L. (Frontiers in Microbiology, 2023)
In the human gastrointestinal tract, the gut mucosa and the bacterial component of the microbiota interact and modulate each other to accomplish a variety of critical functions. These include digestion aid, maintenance of the mucosal barrier, immune regulation, and production of vitamins, hormones, and other metabolites that are important for our health. The mucus lining of the gut is primarily composed of mucins, large glycosylated proteins with glycosylation patterns that vary depending on factors including location in the digestive tract and the local microbial population. Many gut bacteria have evolved to reside within the mucus layer and thus encode mucus-adhering and -degrading proteins. By doing so, they can influence the integrity of the mucus barrier and therefore promote either health maintenance or the onset and progression of some diseases. The viral members of the gut – mostly composed of bacteriophages – have also been shown to have mucus-interacting capabilities, but their mechanisms and effects remain largely unexplored. In this review, we discuss the role of bacteriophages in influencing mucosal integrity, indirectly via interactions with other members of the gut microbiota, or directly with the gut mucus via phage-encoded carbohydrate-interacting proteins. We additionally discuss how these phage-mucus interactions may influence health and disease states.